Merits of Level III Axillary Dissection in Node-Positive Breast Cancer: A Prospective, Single-Institution Study From India - Shalaka Joshi; Jarin Noronha; Rohini Hawaldar; Girish Kundgulwar; Vaibhav Vanmali; Vani Parmar; Nita Nair; Tanuja Shet; Rajendra Badwe (Journal of Global Oncology, 2019)
PURPOSE: A complete axillary lymph node (ALN) dissection is therapeutic in node-positive breast cancer. Presently, there is no international consensus regarding anatomic levels to be addressed in complete axillary dissection. We assessed the burden of disease in level III axilla. MATERIALS AND METHODS: A prospectively maintained database was assessed for 1,591 consecutive patients with nonmetastatic breast cancer registered at Tata Memorial Center, Mumbai, between January 2009 and December 2014. RESULTS: A median of four (zero to 20) level III ALNs were dissected and a median of two (one to 17) nodes were positive. A total of 27.3% (434 of 1,591) patients had level III ALN metastasis, and 4.7% of patients had positive interpectoral nodes. Some 53.2% of patients had level III metastases in the presence of four or more positive level I and II ALNs. A total of 9.4% of patients had level III involvement when one to three ALNs were positive in level I and II (P < .001). Some 53.2% of patients had level III metastases in the presence of four or more positive level I and II ALNs. On logistic regression analysis, four or more positive ALNs in level I or II (P < .001), inner/central quadrant tumor location (P = .013), and perinodal extension (P < .001) were associated with level III ALN involvement. At a median follow-up of 36 months, the disease-free survival was significantly worse for level III ALN metastases on univariate analysis (P < .001). On multivariate Cox regression analysis, histologic grade (P = .006), four or more positive ALNs (P < .001), hormone receptor status (P < .001), and tumor size (P = .037) were independent prognostic factors for disease-free survival. CONCLUSION: The axillary nodal burden is high in patients with breast cancer in developing countries like India. One of two women with four or more positive level I and II ALNs may have residual disease in level III if it is not cleared during surgery. Intraoperative interpectoral space clearance should be considered in the presence of either palpable interpectoral lymph nodes or multiple positive ALNs.